Kolaborasi Orang Tua dan Guru dalam Stimulasi Perkembangan Sosial Emosional Anak Usia Dini - Ernawati Ernawati; Mutmainnah; Rofi’atul Alliah (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2026)
This study is motivated by the importance of family and educational institution involvement in supporting early childhood development. Child development is often understood as a school task, even though the family is the primary environment that plays a significant role in maintaining on going stimulation at home. The purpose of this study is the describe how parents and teachers collaborate to support early childhood development. The method used is a descriptive qualitative case study. The research subjects consisted of teachers, principals, and parents of students. Data collection technique were confucted through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. Data validity was achieved through triangulation of source and technique. The results show that collaboration between parents and teachers occurs in three main ways. Whatsapp group communication, the use of contact books, and regular meetings. These three methods are used to convey information about learning, track children’s progress, and discuss school programs. The implications of this study emphasize that targeted communication between teachers and parents must be strengthened to ensure consistent stimulation of children’s social and emotional development both at school an at home.